2019
DOI: 10.1186/s12879-019-4172-3
|View full text |Cite
|
Sign up to set email alerts
|

Extensive disseminated cysticercosis: a case report in Yunnan province, China

Abstract: Background Cysticercosis is spreading all over the world and it is a major health problem in most countries of Latin America, Africa, and Asia. Extensive disseminated cysticercosis is relatively rare and fewer than 120 case have been reported in the worldwide. We reported a rare case of extensive disseminated cysticercosis in Yunan province, China. Case presentation A rare case of extensive disseminated cysticercosis, in a 61-year-old male Chinese was detected from Yunn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Complete resolution of lesions was observed in 35% of patients, while either reduction in the number of lesions or calcification was observed in the rest of the patients [2]. Of late, several authors have initiated and reported good benefit of anti-cysticidal therapy in patients with disseminated cysticercosis [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Complete resolution of lesions was observed in 35% of patients, while either reduction in the number of lesions or calcification was observed in the rest of the patients [2]. Of late, several authors have initiated and reported good benefit of anti-cysticidal therapy in patients with disseminated cysticercosis [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been a great threat to people’s health in China [ 14 ]. The western parts of China are major local endemic areas now, because traditional husbandry, consumption of raw pork and poor sanitation are common there [ 17 ]. A survey of 484,210 participants from 31 provinces in China from 2014 to 2015 found 1752 positive taeniasis cases through microscopic examination [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neurocysticercosis (NCC) remains the most common cause of acquired epilepsy worldwide 1 . Definitive treatment of this infectious disease involves antiparasitic therapy with praziquantel or albendazole.…”
Section: Figurementioning
confidence: 99%
“…The disseminated variant of cysticercosis is uncommon, with less than 120 cases reported 1 . The cause of extensive dissemination is not very clear.…”
Section: Figurementioning
confidence: 99%